LINGUISTIC HEDGING STRATEGIES IN DONALD TRUMP’S PEACE FORUM SPEECH: A DISCOURSE ANALYSIS - Zhafran Fatih Ananda; Puteri Anugrah Septianingsih; Febry Aurlani (Universitas Islam Sumatera Utara (UISU), 2026)
This study examines hedging strategies in a contemporary diplomatic speech delivered by Donald Trump, focusing on how epistemic stance is calibrated in a high-stakes political context. Drawing on Hyland’s (1998, 2005) metadiscourse framework, the study employs qualitative discourse analysis alongside frequency-based identification of hedging devices. The analysis identifies 34 instances of hedging, with lexical judgmental verbs such as I think, and I believe constituting the dominant category (62%), followed by modal auxiliaries including may and might. The findings show that hedging is systematically clustered in discourse segments addressing future negotiations and geopolitical uncertainty, while more assertive constructions are used when referring to past achievements. This patterned alternation suggests a form of controlled epistemic modulation, defined in this study as the deliberate calibration of commitment strength in response to contextual volatility and diplomatic risk. Rather than signaling weakness or indecision, hedging in the analyzed speech functions as a rhetorical resource for balancing authority and negotiability, contributing to the construction of a diplomatic yet assertive leadership persona. The study offers a refined perspective on metadiscourse by highlighting the central role of lexical hedging verbs in political stance management and proposing a nuanced account of epistemic modulation in contemporary diplomacy.